A prediction model for sudden cardiac death in patients with heart failure and preserved ejection fraction. (10th October 2014) - Adabag, Selcuk; Rector, Thomas S.; Anand, Inder S.; McMurray, John J.; Zile, Michael; Komajda, Michel; McKelvie, Robert S.; Massie, Barry; Carson, Peter E.
<x xml:space="preserve">Abstract</x> Aims Sudden cardiac death (SCD) accounts for ∼ 25% of all deaths in heart failure with preserved ejection fraction (HFpEF). However, strategies to identify HFpEF patients at a higher risk of SCD have not been developed. Methods and results We studied 4128 patients with HFpEF enrolled in the Irbesartan in Patients with Heart Failure and Preserved Ejection Fraction (I‐PRESERVE) trial. All SCDs were adjudicated by a clinical endpoint committee. Cumulative incidences of SCD were estimated counting other deaths as competing risks. Cox regression analysis was used to generate a risk model for SCD. During a mean follow‐up of 4.1 years, 231 (5.6%) patients died suddenly and 650 (15.7%) died non‐suddenly. A multivariable model in 3480 patients including age, gender, history of diabetes and myocardial infarction, LBBB on ECG, and the natural logarithm of NT‐proBNP identified a subgroup of 837 (24%) patients with ≥10% cumulative incidence of SCD over 5 years, accounting for other deaths as competing risk (Harrell's C index 0.75). The 5‐year cumulative incidences of SCD in the higher and lower risk groups were 11% and 4%, respectively. In the higher risk group, 32% of deaths were SCD compared with 26% in the entire I‐PRESERVE cohort. Conclusions A multivariable prediction model identified patients with HFpEF who have a ≥10% risk of SCD over 5 years, similar to the risk of SCD in the Sudden Cardiac Death in Heart Failure (SCD‐Heft) trial. This model may be useful for selecting patients with HFpEF for SCD prevention trials.